2016
DOI: 10.1002/eqe.2721
|View full text |Cite
|
Sign up to set email alerts
|

The effect of causal parameter bounds in PSHA‐based ground motion selection

Abstract: SUMMARYIn this paper the effect of causal parameter bounds (e.g. magnitude, source-to-site distance, and site condition) on ground motion selection, based on probabilistic seismic hazard analysis (PSHA) results, is investigated. Despite the prevalent application of causal parameter bounds in ground motion selection, present literature on the topic is cast in the context of a scenario earthquake of interest, and thus specific bounds for use in ground motion selection based on PSHA, and the implications of such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…We do not specify a selection constraint on M w and R rup , because it would have a similar effect as scaling limit in the selection process. Besides, to select a suite of ground motions with similar site characteristics, a selection constraint on V s30 (time‐averaged shear wave velocity in the upper 30 m of a soil profile) suggested by Tarbali and Bradley is adopted. As shown in Table , only records with V s30 between 0.5 and 1.5 times the site V s30 value are considered as candidate ground motions.…”
Section: Seismic Hazard Analysis and Ground Motion Datasetmentioning
confidence: 99%
“…We do not specify a selection constraint on M w and R rup , because it would have a similar effect as scaling limit in the selection process. Besides, to select a suite of ground motions with similar site characteristics, a selection constraint on V s30 (time‐averaged shear wave velocity in the upper 30 m of a soil profile) suggested by Tarbali and Bradley is adopted. As shown in Table , only records with V s30 between 0.5 and 1.5 times the site V s30 value are considered as candidate ground motions.…”
Section: Seismic Hazard Analysis and Ground Motion Datasetmentioning
confidence: 99%
“…This assumption is made on the condition that "Task 1" has been completed appropriately. However, this is often not the case, as illustrated in [12,15].…”
Section: Figure 2: Examples Of Ground Motion Amplitude-scaling For Mamentioning
confidence: 99%
“…This recognises the fact that it is not simply the properties of the modelled hazard that determine these bin sizes, but also the availability of recordings arising from similar rupture scenarios. Additionally, it has been demonstrated that duration and cumulative effects cannot be fully accounted for by using causal parameter bins if only spectral accelerations at different periods are used as intensity measures . Therefore, values of the causal parameters (ie, magnitude, distance, etc) should not be the primary factors considered when selecting a set of ground motions.…”
Section: Introductionmentioning
confidence: 99%
“…Although several general recommendations have been made, [8][9][10] the optimal ranges of magnitude and distance used to build a bin will vary depending upon the specific problem. 10 This recognises the fact that it is not simply the properties of the modelled hazard that determine these bin sizes, but also the availability of recordings arising from similar rupture scenarios. Additionally, it has been demonstrated that duration and cumulative effects cannot be fully accounted for by using causal parameter bins if only spectral accelerations at different periods are used as intensity measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation